Event-triggered non-fragile finite-time guaranteed cost control for uncertain switched nonlinear networked systems. (May 2020) - Liu, Yurong; Arumugam, Arunkumar; Rathinasamy, Sakthivel; Alsaadi, Fuad E.
Abstract: In this paper, the finite-time event-triggered and guaranteed non-fragile cost control problem is discussed for a class of uncertain switched nonlinear networked control systems (SNNCS) which involves parameter uncertainties and time-varying transmission delays. The main aim of this work is to synthesize finite-time event-triggered and guaranteed cost non-fragile controller for ensuring the finite-time boundedness of the resulting SNNCS with optimal dissipative performance index. By proposing an appropriate Lyapunov–Krasovskii functional and using the average dwell time technique, a set of new delay-dependent finite-time boundedness conditions is established in terms of linear matrix inequalities to obtain the desired result. The proposed approach unifies the H ∞, L 2 − L ∞, passivity and ( Q, S, R ) - dissipativity performance concept in a single framework. Further, the associated optimization problem is formulated to minimize the guaranteed cost performance bound. To save communication resources, an event-based rule is also introduced and implemented for the control signal transmission. Finally, two numerical examples with simulations are provided to demonstrate the efficiency of the developed control design technique.